ENHANCEMENT OF RESENSI TEXT LEARNING USING THE PROBLEM-BASED LEARNING MODEL - Aswin Dwi Nurfadhillah; Lulu'diah Sri Purwati; Eli Syarifah Aeni; Dida Firmansyah (Kopertis Region IV Jabar and Banten, 2019)
This research is motivated by the curiosity of researchers regarding the ability of students to write review texts from the results of the pretest and posttest using the problem based learning model. The formulation of the problem in this study is 1) is learning using the problem based learning model suitable for the review text? 2) What are the results obtained by students regarding review text learning by using a problem based learning model? Based on the existing problem formulation, the purpose of this study is: 1) to find out learning using the problem based learning model suitable in the text of review. 2) to find out the results obtained by students regarding review text learning by using a problem based learning model. This research method is a quantitative descriptive method that will describe the results obtained by students. So, the model of problem based learning is suitable to be used in the study of reviewer texts because by using this model the results of a significant increase are 52% from the pretest to the posttest.